PENDIDIKAN YANG MEMBEBASKAN MASYARAKAT WAIMITE DARI KEMISKINAN - Yohanes Parihala; Rolland A Samson (Program Pascasarjana UKIM, 2019)
The reality of poverty is a serious problem for the people in Maluku. Based on the data from the Central Statistics Agency, it shows that Maluku still occupies the fourth position as the poorest province in Indonesia until the first semester of the Periode in March 2018. The phenomenon of poverty here will be researched in the context of poverty experienced by the community in village of Waemite, Kabupaten Buru, Province of Maluku. The community experiences isolation from the development process which results in poverty shackled communities. In addition, one of the practices of local culture ia tutu mo, deadly critical awareness of society. The cultural practice explicitly forbids the people in Waemite for going to school or studying and have higher educational. Education for liberation is a concept of learning to the community both formally (in school education) and informally (religious or community education) aimed at constructing knowledge and critical awareness from and for the community so that it can move a struggle to break the chain of poverty. This research uses a qualitative research method, which explores the ethical and ethical nature of the experience of the poor and various studies related to poverty.